Solar pv system with pulsating heat pipe cooling - E. Roslan; I Hassim (Institute of Advanced Engineering and Science, 2019)
Malaysia is blessed with high irradiance, making it suitable for solar photovoltaic installation for electricity generation. However, due to the broad wavelength of the solar irradiance, not all wavelength can be converted to electricity due to the limitation of the materials used for the photovoltaic. The infrared radiation absorbed produces heat, and coupled with high surrounding temperature, increases the temperature of the photovoltaic panel thus decreasing it efficiency. This paper presents the study of the effect of attaching pulsating heat pipe at the back of solar panel as a means of passive cooling. Pulsating heat pipe is a recent discovery in the heat pipe industry, introduced in 1996 by Akachi but has not been used for the purpose of cooling solar panels. This study shows the maximum difference between 5 Celsius between the pulsating heat pipe cooled panel and the reference panel without any cooling, resulting in 0.77% increase in electrical output efficiencyMalaysia is blessed with high irradiance, making it suitable for solar photovoltaic installation for electricity generation. However, due to the broad wavelength of the solar irradiance, not all wavelength can be converted to electricity due to the limitation of the materials used for the photovoltaic. The infrared radiation absorbed produces heat, and coupled with high surrounding temperature, increases the temperature of the photovoltaic panel thus decreasing it efficiency. This paper presents the study of the effect of attaching pulsating heat pipe at the back of solar panel as a means of passive cooling. Pulsating heat pipe is a recent discovery in the heat pipe industry, introduced in 1996 by Akachi but has not been used for the purpose of cooling solar panels. This study shows the maximum difference between 5 Celsius between the pulsating heat pipe cooled panel and the reference panel without any cooling, resulting in 0.77% increase in electrical output efficiency.